2016
DOI: 10.20452/pamw.3447
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the effectiveness of hypercholesterolemia treatment following hospitalization for coronary artery disease

Abstract: in patients with CAD. 1,2 One of the most important risk factors is hypercholesterolemia, while the use of statins is related to improved prognosis. The European guidelines recommend lowering low-density lipoprotein (LDL) cholesterol levels below 1.8 mmol/l in all coronary patients. 3,4 INTRODUCTION Patients with established coronary artery disease (CAD) are at high risk of recurrent cardiovascular events. Despite advances in pharmacological and invasive treatment methods, a number of risk factors remain indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 1 publication
0
12
1
3
Order By: Relevance
“…Jankowski at al. [46] pointed out different healthcare-related factors and patient-related factors affecting proper treatment of patients with cardiovascular diseases. According to Jankowska-Polanska at al.…”
Section: Discussionmentioning
confidence: 99%
“…Jankowski at al. [46] pointed out different healthcare-related factors and patient-related factors affecting proper treatment of patients with cardiovascular diseases. According to Jankowska-Polanska at al.…”
Section: Discussionmentioning
confidence: 99%
“…In the Polish part of the EUROASPIRE IV study, over 80% of patients were taking lipid-lowering medication (36% statins at high dose). 22,23 Nevertheless, overall, only about 25% were at treatment target of LDL-C of less than 1.8 mmol/l, which is, in any case, a 2-fold difference from the very high-risk group in the general population. 22,23 The use of moderate-intensity and high-intensity statin therapy in WOBASZ II seems to be more frequent than that found in the 3ST-POL study of nearly 50 000 ambulatory patients in Poland before 2010, in which almost 71% of patients received the daily statin dose of less than 20 mg.…”
Section: 47mentioning
confidence: 95%
“…19,20 The second frequent risk factor in our study was hypertension, observed in over 40% of the patients. The incidence of hypertension in young patients with AMI seems to have increased over the years.…”
Section: Data Collectionmentioning
confidence: 57%